Digital transformation for more nutritious food systems: How digital tools can be used to scale and commercialize nutrient-enriched staple crops - Walton, Jenny; Brown, Lynn; Storr, Samuel (International Food Policy Research Institute, 2023)
This paper explains the need for digital tools and how they enable commercialization and scale, the impact on users, and the risks and benefits with examples of projects and partners along the value chain. This approach is being applied across all HarvestPlus activities and digital projects are researched and reported as part of the CGIAR Digital Innovation Initiative.